Harmonizing Legal Positivism and Natural Law for Social Engineering: Addressing Child Marriage in Indonesian Indigenous Communities - Tan, Winsherly; Kalita, Manashi; Rusdiana, Shelvi; Situmeang, Ampuan; Seroja, Triana Dewi (SASI, 2026)
Introduction: This article examines the normative tension between state law and customary law in regulating child marriage practices within indigenous communities. In the Indonesian legal system, marriage is regulated through a formal legal framework emphasizing legal certainty and protection, while customary practices are rooted in communal values, traditions, and unwritten norms. Within the perspective of legal pluralism, the coexistence of these legal systems often creates challenges in terms of effectiveness, compliance, and social legitimacy. Purposes of the Research: The purpose of this research is to analyze the application of legal positivism and natural law theory in social engineering toward child marriage practices in indigenous communities, as well as to formulate an appropriate approach for addressing such practices within the framework of Indonesian law. Methods of the Research: This research employs a normative juridical method using statute and conceptual approaches. Legal materials consist of primary sources such as legislation and secondary sources including legal doctrines and scholarly writings related to customary law, marriage law, and legal theory. Results of the Research: The findings reveal that the persistence of child marriage in indigenous communities reflects a normative tension between the formal validity of state law and the moral legitimacy of customary law. Neither legal positivism nor natural law independently provides an adequate solution. Instead, an integrative approach based on Roscoe Pound's concept of law as social engineering, supported by legal positivism and natural law, offers a more effective framework for promoting legal reform while respecting indigenous cultural values. This study contributes to the literature by proposing an integrated analytical framework that bridges legal certainty, moral legitimacy, and participatory social transformation in legally pluralistic societies.